Mutation Analysis of Consanguineous Moroccan Patients with Parkinson’s Disease Combining Microarray and Gene Panel - Bouhouche, Ahmed; Tesson, Christelle; Regragui, Wafaa; Rahmani, Mounia; Drouet, Valérie; Tibar, Houyam; Souirti, Zouhayr; Ben El Haj, Rafiqua; Bouslam, Naima; Yahyaoui, Mohamed; Brice, Alexis; Benomar, Ali; et al. (Frontiers in Neurology, 2017)
During the last two decades, 15 different genes have been reported to be responsible for the monogenic form of Parkinson's disease (PD), representing a worldwide frequency of 5-10%. Among them, 10 genes have been associated with autosomal recessive PD, with PRKN and PINK1 being the most frequent. In a cohort of 145 unrelated Moroccan PD patients enrolled since 2013, 19 patients were born from a consanguineous marriage, of which 15 were isolated cases and 4 familial. One patient was homozygous for the common LRRK2 G2019S mutation and the 18 others who did not carry this mutation were screened for exon rearrangements in the PRKN gene using Affymetrix Cytoscan HD microarray. Two patients were determined homozygous for PRKN exon-deletions, while another patient presented with compound heterozygous inheritance (3/18, 17%). Two other patients showed a region of homozygosity covering the 1p36.12 locus and were sequenced for the candidate PINK1 gene, which revealed two homozygous point mutations: the known Q456X mutation in exon 7 and a novel L539F variation in exon 8. The 13 remaining patients were subjected to next-generation sequencing that targeted a panel of 22 PD-causing genes and overlapping phenotypes. NGS data showed that two unrelated consanguineous patients with juvenile onset PD (12 and 13 years) carried the same homozygous stop mutation W258X in the ATP13A2 gene, possibly resulting from a founder effect; and one patient with late onset (76 years) carried a novel heterozygous frameshift mutation in SYNJ1. Clinical analysis showed that patients with the ATP13A2 mutation developed juvenile-onset PD with a severe phenotype, whereas patients having either PRKN or PINK1 mutations displayed early-onset PD with a relatively mild phenotype. By identifying pathogenic mutations in 45% (8/18) of our inbred Moroccan PD series, we demonstrate that the combination of chromosomal microarray analysis and next-generation sequencing is a powerful approach to pinpoint the genetic bases of autosomal recessive PD, particularly in countries with a high rate of consanguinity.